Lecture analytique de deux récits de Montesquieu et Voltaire, écrivains-philosophes du XVIIIème siècle. - Breibech, Fadwa Fakhri (مجلة كلية الاداب, 2022)
In the 18th century, the age of enlightenment, science, and knowledge, philosophers wrote various texts to spread their ideas that call for development, modernization, and the shedding of the old religious and cultural traditions alongside renouncing intolerance, social inequality, and intellectual terrorism. Among the philosophers of this age emerged the French philosophers Voltaire and Montesquieu whose thoughts and philosophies framed the French revolution. In 1721 Montesquieu wrote the novel Lettrespersanes (Persian Letters) and Voltaire followed in 1767 with the philosophical fiction novel L'Ingénu(The Huron). The shared influences and similarities between these two works, Persian Letter and The Huron, demand that we shed light upon these two texts through a modern and analytical perusal. Which would lead to understanding the extent of influence and similarity between the philosophers of the enlightenment age, who had a direct impact on the French revolution and its transition from absolute equality through savage terror and finally into a totalitarian empire, and our current age wrought with contradictions. Were the philosophers of that age truly able to destroy the old regime and replace it with a new one through thought?